Technical Assistance in Producing Alternative Feed Using Silage Techniques to Boost Productivity Among Duck Farmers in Buket Pulo Village - Maulida Sari; Prima Nucifera; Weni Astari; Nur Amelia; Putri Amilda Amilda (Universitas Ahmad Dahlan, 2026)
Background: The village of Buket Pulo has potential for duck farming development. However, farmers’ limited knowledge and skill in processing alternative feed using silage techniques have resulted in high production costs and suboptimal livestock productivity. Contribution: This community service activity aims to improve farmers’ skills in producing alternative feed using silage techniques by utilizing local waste as a sustainable feed source. The activity integrates participatory mentoring and hands-on practice to improve farmers’ technical capacity in feed production. Method: This study employed a quantitative descriptive approach combined with the participatory action research (PAR) method. Participants were selected through purposive sampling. Data collection was conducted via pre-test and post-test, observation, and focus group discussion (FGDs). The data were analyzed descriptively to assess improvements in participants’ knowledge and skills. Results: Training on the production of alternative feed using silage techniques demonstrated an increase in farmers’ knowledge, as evidenced by the difference between the pre-test score (40,6) and the post-test score (86,6), representing a 113% increase. In addition, observations of participants’ practical skills yielded an average score of 88,6%, which falls in to the very good category. Conclusion: The results of the activity indicate that guidance on the production of alternative feed using silage techniques is effective in improving farmers’ knowledge and skills. This participatory guidance model has the potential to be applied to other farming communities to support increased productivity and efficiency in livestock farming.